Lexicon Analysis in Sampi Gerumbungan Dance Costume - Ni Putu Sintia Dewi Kusuma Wardani; I Gede Budasi; Putu Eka Dambayana (Linguistic, English Education and Art (LEEA) Journal, 2023)
The study aims to find out what are lexicons used in the Sampi Gerumbungan dance in the costumes and its cultural meaning. The method used in this study is a descriptive qualitative design. The method directs researchers in obtaining social information accurately, broadly, and completely by designing problem formulations. The results of this study found that there were sixteen (16) lexicons found in the costumes of the Sampi Gerumbungan dance. All lexicons in the costumes are also classified based on parts of body, namely head costumes (5 lexicons), neck costumes (2 lexicons), hand costume (1 lexicon), body costumes (8 lexicons), and leg costume (1 lexicon). It can be concluded that there are several lexicons used in the Sampi Gerumbungan dance costumes and have cultural meanings. Keywords: Costume, Ecolinguistics, Lexicon, Sampi Gerumbungan Dance